Scalp Acupuncture on the Immediate and Prolonged Motor Recovery in Spinal Cord Injury: a Case Report - Geetha B. Shetty; Nanjeshgowda H L (Medical Association of Pharmacopuncture Institute, 2023)
Spinal cord injury (SCI) is one of the main causes of lifelong motor impairment and is associated with important secondary complications. Thus, multifaceted treatments are needed for early functional recovery. Currently, in cases of SCI, surgery, stem cell treatment, medication, and physical therapy are used to repair and restore neuronal activity. Additionally, encouraging results have been reported on the use of acupuncture to modulate neuronal plasticity. Here, we present an SCI case involving a burst fracture at the L3 level, which was treated for 21 days using scalp acupuncture with residential physical therapy. Activation of the motor area was observed after the 1st day of treatment, with the patient completely regaining power and range of motion in the knees, Additionally, over 21 days, the patient exhibited markedly improved motor recovery and functional outcomes, which had not been observed over the previous six months. This report highlights the importance of complementing scalp acupuncture with intensive physical therapy for better motor recovery.